New Exact Structures for the Nonlinear Lattice Equation by the Auxiliary Fractional Shape (Journal of Partial Differential Equations, 2016)
In this paper, the auxiliary rational shape is successfully applied for obtaining new exact travelling solutions of the nonlinear lattice equation. These solutions include rational solutions, with periodic and doubly periodic wave profiles. Many new exact traveling wave solutions are successfully obtained.
Keywords: Nonlinear lattice; travelling wave solutions